Self-Regulation and Academic Measures Across the Early Elementary School Grades: Examining Longitudinal and Bidirectional Associations. Issue 7 (3rd October 2018) - Hernández, Maciel M.; Eisenberg, Nancy; Valiente, Carlos; Spinrad, Tracy L.; Johns, Sarah K.; Berger, Rebecca H.; Silva, Kassondra M.; Diaz, Anjolii; Gal-Szabo, Diana E.; Thompson, Marilyn S.; Southworth, Jody
ABSTRACT: This study evaluated the association between children's ( N = 301) self-regulation and math and reading achievement in kindergarten, 1st grade, and 2nd grade. Children's self-regulation was assessed using the Head–Toes–Knees–Shoulders (HTKS) task (involving control of gross body movements) and a computerized continuous performance task (CPT; assessing primarily inhibitory control) in kindergarten, 1st grade, and 2nd grade. Research Findings : Based on cross-lagged structural equation panel models, HTKS task performance positively predicted later math and reading achievement. Math achievement significantly and positively predicted later HTKS and CPT scores. Earlier math and reading achievement moderated the association between CPT scores and later math and reading achievement; inhibitory control–based self-regulation assessed with the CPT predicted higher math or reading achievement in subsequent grades for children with lower math or reading achievement in prior grades. Performance on the CPT moderated the paths from HTKS scores to later reading achievement; behavioral self-regulation assessed with the HTKS task predicted higher reading achievement in subsequent grades for children with low or average CPT performance in prior grades. Practice or Policy : Results from this study have the potential to inform targeted academic interventions focused on enhancing self-regulation in school contexts. The findings highlight the utility of assessing multiple measures of self-regulation.